Librarians and Information Professionals Personality Traits and Their Correlation with Their Job Statisfaction: Case Study of Special and Research Libraries in Metro Tehran - Seyyedeh Sepideh Seyyed Asgari; N Naghshineh; R Rostami; Masoud Lavasani (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2011)
Objective: The present study investigates the linkage between personality profile of librarians and information professionals working at special and research libraries in metropolitan Tehran with their job satisfaction. Methodology: A survey was conducted using NEO Five-Factor Inventory (NEO-FFI) as well as Job Satisfaction Survey (JSS) as data collection instruments. Sample was drawn from those librarians and information professionals who were currently employed with a special or research library in Tehran, Findings: Data analysis indicated that neuroticism and agreeableness have negative significance with the overall job satisfaction. Findings do not indicate any significance between job satisfaction with demographics such as age and work experience. They further indicate that men demonstrate more satisfaction with their jobs than women.